Automatic hepatitis diagnosis system based on Linear Discriminant Analysis and Adaptive Network based on Fuzzy Inference System - Dogantekin, Esin; Dogantekin, Akif; Avci, Derya (Pergamon-Elsevier Science Ltd, 2009)
In this paper, an automatic diagnosis system based on Linear Discriminant Analysis (LDA) and Adaptive Network based on Fuzzy Inference System (ANFIS) for hepatitis diseases is introduced. This automatic diagnosis system deals with the combination of feature extraction and classification. This automatic hepatitis diagnosis system has two stages, which feature extraction - reduction and classification stages. In the feature extraction - reduction stage, the hepatitis features were obtained from LICI Repository of Machine Learning Databases. Then, the number of these features was reduced to 8 from 19 by using Linear Discriminant Analysis (LDA). In the classification stage, these reduced features are given to inputs ANFIS classifier. The correct diagnosis performance of the LDA-ANFIS automatic diagnosis system for hepatitis disease is estimated by using classification accuracy, sensitivity and specificity analysis, respectively. The classification accuracy of this LDA-ANFIS automatic diagnosis system for the diagnosis of hepatitis disease was obtained in about 94.16%. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Linear Discriminant Analysis (LDA); Adaptive Network based on Fuzzy Inference System (ANFIS); Hepatitis database; Automatic system; Classification accuracy; Sensitivity and specificity analysis